Role of flavonoids in controlling obesity: molecular targets and mechanisms - Mahboob, Anns; Samuel, Samson Mathews; Mohamed, Arif; Wani, Mohmmad Younus; Ghorbel, Sofiane; Miled, Nabil; Büsselberg, Dietrich; Chaari, Ali (Frontiers in Nutrition, 2023)
Obesity presents a major health challenge that increases the risk of several non-communicable illnesses, such as but not limited to diabetes, hypertension, cardiovascular diseases, musculoskeletal and neurological disorders, sleep disorders, and cancers. Accounting for nearly 8% of global deaths (4.7 million) in 2017, obesity leads to diminishing quality of life and a higher premature mortality rate among affected individuals. Although essentially dubbed as a modifiable and preventable health concern, prevention, and treatment strategies against obesity, such as calorie intake restriction and increasing calorie burning, have gained little long-term success. In this manuscript, we detail the pathophysiology of obesity as a multifactorial, oxidative stress-dependent inflammatory disease. We describe how several naturally occurring flavonoid compounds can be used to prevent and treat obesity with long